Entre duas águas: correntes terapêuticas franco-brasileiras no processo de balnearização do Rio de Janeiro - Antoine Huerta (Confins)
Rio de Janeiro in the 19th century, the practice of sea baths was at that time under the influence of French doctors and physicists who propagated it for preventive and curative purposes. Some of them lived in this country or stayed there long enough to facilitate the diffusion of their thought about seabathing. They encouraged the practice of therapeutic bathing in their works which were widely read within the educated population. Their impact was quite remarkable on the development of balneotherapy in Brazil and this hygienist discourse had a singular force of modification of the urban space. A qualitative approach of this evolution will show the most salient aspects of French medical involvement in the balnearization process of Rio de Janeiro. Cultural transfers and intermediary actors who promoted the medical models have contributed to the emergence of the Brazilian thermal culture.